Numerical simulation of the nanofluid flow and heat transfer in porous microchannels with different flow path arrangements using single-phase and two-phase models - Farnaz Sanei; Ali B. M․ Ali; Dheyaa J. Jasim; Soheil Salahshour; Omid Ali Akbari; Nafiseh Emami (International Journal of Thermofluids)
Background: The fluid flow and nanofluid heat transfer are studied in this research through porous microchannels with different flow path arrangements in single-phase and two-phase modes (Mode I and Mode II). In Mode I, the flow inlet is located in the longitudinal direction of the microchannel (single-way path), while in Mode II, the flow inlet is placed in the transverse direction of the microchannel (two-way path). Methods: The finite volume method was utilized to simulate the flow and heat transfer. The porous medium is supposed homogeneous and isotropic with a porosity coefficient of 0.9 and it is assumed that the local thermal equilibrium is established between the fluid and the solid. The Eulerian-Eulerian mixture model is applied for modeling the two-phase flow. As demonstrated, mode II always has a higher heat transfer rate than mode I. However, in contrast, the pressure drop of mode I is lower than in mode II. Besides, using the two-phase model predicts a higher heat transfer rate than the single-phase model in all cases. Significant Findings: The percent increase of pressure in mode II compared to mode I in Re= 100 and 400 is obtained as 11.5 % and 20.8 %, respectively. At Re= 100 in mode I, the heat transfer percentage increases by 52.6 % from Da=1 compared to a case without the porous foam. Whilst, at Re= 400, the rise is found to be 45.5 %. In mode II, at Re=100, the heat transfer percentage increases by 63.9 % from Da= 1 compared to a case without the porous foam. Whilst, at Re= 400, the rise is found to be 43.3 %. Finally, Mode II microchannel has more heat transfer rate and pressure drop than Mode I.